A Typical MRI Features of Wernicke’s Encephalopathy: A Case Report - Khuvituguldur, Telmen; Dagvasumberel, Munkhbaatar; Khashbat, Delgerdalai (Central Asian Journal of Medical Sciences, 2024)
Objective: This case report highlights the rare occurrence of Wernicke encephalopathy (WE) in a non-alcoholic patient with atypical imaging findings. Methods: Diagnosis is made based on clinical and imaging findings. Results: A 44-year-old man with a history of inability to walk, ataxia, and did not have a habit of alcoholism. Magnetic resonance imaging (MRI) showed symmetrical bilateral basal ganglia changes. Conclusion: We should always be included in the differential diagnosis for bilateral basal ganglia lesions. MRI has proven useful in diagnosing WE in patients with occasional neurological symptoms and atypical imaging findings.